Deposition of polychlorinated biphenyls and polybrominated diphenyl ethers in the vicinity of a steel manufacturing plant - Fang, Mingliang; Choi, Sung-Deuk; Baek, Song-Yee; Jin, Guangzhu; Chang, Yoon-Seok (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Spatial distribution and seasonal variation of polychlorinated biphenyl (PCB) and polybrominated diphenyl ether (PBDE) bulk deposition were investigated at four sites at and around an iron and steel making plant in Pohang, South Korea from January 2008 to May 2009. The steel complex site showed the highest average deposition fluxes of 74.0, 2.1, and 41.6 ng m(-2) day(-1) for Sigma tri-decaPCBS (Tri-DecaCBs), Sigma(12)PCBs (dioxin-like PCBs), and Sigma 8PBDEs (8 PBDE congeners), respectively, indicating the steel complex is an important source of PCBs and PBDEs. The PCB deposition was dominated by Tri-TetraCBs and BDE209 was the most abundant PBDE congener. No clear seasonal variation of PCB and PBDE deposition was observed except at the steel complex site. Precipitation appeared to play an important role in the deposition distribution of PCBs, especially when the lowly chlorinated homologues dominated. In addition, the contribution of DL PCBs (dioxin-like PCBs) to the total TEQ(toxicity equivalent quantity) showed a seasonal variation and should not be neglected in the vicinity of a steel complex. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; DIBENZO-P-DIOXINS; ATMOSPHERIC BULK DEPOSITION; WET DEPOSITION; DRY DEPOSITION; PBDES; PCBS; IRON; EMISSIONS; AREAS